2011
DOI: 10.1007/s00066-011-2248-0
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Decreases Survival of Hep3B Liver and MCF-7 Breast Cancer Cells

Abstract: Effects of curcumin on cell growth and survival factor expression suggest its potential benefit in the treatment of cancer without a direct radiosensitizing influence of curcumin on these cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(42 citation statements)
references
References 49 publications
3
38
0
1
Order By: Relevance
“…Curcumin potently inhibited HIF1A protein production both in rodent endocrine pituitary tumour cell lines and in cells of different human pituitary adenoma types. This has also been observed for curcumin and its derivatives in a variety of cell lines serving as models of different types of tumours (Bae et al 2006, Thomas et al 2008, Jung et al 2010, Ströfer et al 2011.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Curcumin potently inhibited HIF1A protein production both in rodent endocrine pituitary tumour cell lines and in cells of different human pituitary adenoma types. This has also been observed for curcumin and its derivatives in a variety of cell lines serving as models of different types of tumours (Bae et al 2006, Thomas et al 2008, Jung et al 2010, Ströfer et al 2011.…”
Section: Discussionsupporting
confidence: 52%
“…In a series of carcinoma cell lines, it has been shown that curcumin was not able to affect HIF1A production but suppressed HIF1 by down-regulating HIF1B (aryl hydrocarbon receptor nuclear translocator (ARNT)), the hypoxia-independent subunit of HIF1 (Choi et al 2006). In other cell types, curcumin concomitantly suppressed HIF1A and HIF1B (Ströfer et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, curcumin facilitated the degradation of ARNT and blocked HIF signalling [14]. Similar effects were reported by Ströfer et al [15]. Curcumin-mediated ARNT depletion was observed in human HepG2, Hep3B and MCF-7 cells [15].…”
Section: Upregulation Of Arnt In Response To Hypoxiasupporting
confidence: 76%
“…Це жовтий пігмент, отриманий з коренів рослини Curcuma longa, який використову-ється як біологічно активна добавка в терапії атеросклерозу, цукрового діабету, при алер-гічних захворюваннях. Він має протектив-ний ефект при пошкодженнях міокарда [8], впливає на активність цитокінів, ензимів та транскрипційних факторів, пов'язаних із гіпоксією [9], а також зменшує токсичний вплив доксорубіцину на серце, печінку та нирки за рахунок його антиоксидантних властивостей [10][11][12]. Водночас комплексне вивчення протективного ефекту куркуміну на мітохондріальний апарат кардіоміоцитів при застосуванні антрациклінів досі не про-водилося.…”
Section: вступunclassified